Melanogenic effect of dersimelagon (MT‐7117), a novel oral melanocortin 1 receptor agonist. Issue 1 (29th November 2021) - Suzuki, T.; Kawano, Y.; Matsumoto, A.; Kondo, M.; Funayama, K.; Tanemura, S.; Miyashiro, M.; Nishi, A.; Yamada, K.; Tsuda, M.; Sato, A.; Morokuma, K.; et al.
Abstract: Background: The activation of melanocortin 1 receptor (MC1R) on melanocytes stimulates the production of eumelanin. A tridecapeptide α melanocyte‐stimulating hormone (αMSH) is known to induce skin pigmentation. Objectives: We characterised the properties of a novel oral MC1R agonist dersimelagon (MT‐7117) with respect to its specific binding to MC1R, downstream signalling and eumelanin production in experimental models. Methods: The competitive binding and production of intracellular cyclic adenosine 3′, 5′‐monophosphate in cells expressing recombinant melanocortin receptors were examined. A mouse melanoma cell line B16F1 was used for the evaluation of in vitro melanin production. The in vitro activity of MT‐7117 was determined with αMSH and [Nle 4, D‐Phe 7 ]‐αMSH (NDP‐αMSH) as reference comparators. The change of coat colour and skin pigmentation were evaluated after repeat administration of MT‐7117 by oral gavage to C57BL/6J‐A y /+ mice and cynomolgus monkeys, respectively. Results: MT‐7117 showed the highest affinity for human MC1R compared to the other melanocortin receptors evaluated and agonistic activity for human, cynomolgus monkey and mouse MC1R, with EC50 values in the nanomolar range. In B16F1 cells, MT‐7117 increased melanin production in a concentration‐dependent manner. In vivo, MT‐7117 (≥0.3 mg/kg/day p.o.) significantly induced coat colour darkening in mice. MT‐7117 (≥1 mg/kg/day p.o.) induced significant skin pigmentation in monkeys and complete reversibility was observed after cessation of its administration. Conclusions: MT‐7117 is a novel oral MC1R agonist that induces melanogenesis in vitro and in vivo, suggesting its potential application for the prevention of phototoxic reactions in patients with photodermatoses, such as erythropoietic protoporphyria and X‐linked protoporphyria. Abstract :